(untitled) - Robertson, Lesley Anne (Cambridge, 2000)
Simple Program Design allows readers to develop sound programming skills for solving common business problems. Stressing structured programming and modular design, this book uses pseudocode as the major design technique. Language-independent explanations provide a strong foundation in program design problem solving.
Keywords: Computer programming,Chương trình máy tính